The Effect of the Augmented Reality Applications in Science Class on Students’ 21st Century Skills and Basic Skills - Irem Dilmen; Nurhan Atalay (Universitas Pendidikan Indonesia, 2021)
This study investigates augmented reality (AR) applications on 21st-century skills and basic skills of elementary school students. The research method is determined as a mixed method. The sample group of the research consisted of 62 randomly selected elementary school 4th-grade students. In the experimental group, courses were taught using AR, and in the control group, the lessons were taught with activities included in the science class. In the research, the 21st-century learning and innovation scale and basic skills scale was used as a quantitative data collection tool, and semi-structured interview and researcher's journal were used as a qualitative data collection tool. According to the results, the study of science using augmented reality applications has positively affected the skills of elementary school 4th-grade students. The qualitative results of the research concluded that students' creativity and innovation, critical thinking, making inferences, problem-solving, collaboration, and communication skills developed. During the interviews with students and the classroom teacher, they stated that the AR application makes information more permanent by embodying the information in their minds. The lessons are fun and exciting; their interest in technology is increased and should be used in other lessons.